Effects of Bene (Pistacia atlantica) on Histopathology of Testis, Sperm Chromatin Quality and Stress Oxidative in Busulfan-Induced Infertile Mice - Hojat Norasteh; Shabnam Mohammadi; Mohammad Reza Nikravesh; Samaneh Broumand; Farimah Beheshti (Tabriz University of Medical Sciences, 2019)
Background: Some plants stimulate spermatogenesis and increase fertility, while some cause spermatogenesis arrest. So far, the effects of bene (Pistacia atlantica) on male fertility have not been studied. The aim of this study was to investigate the effects of bene on sperm parameters, testicular histopathology, sperm quality, and oxidative stress in busulfan-induced infertile mice. Methods: Thirty-five male BALB/c mice were randomly assigned to control, sham, busulfan, bene, and bene + busulfan groups. The busulfan group received 10 mg/kg as a single dose and intraperitoneally. The bene group received pellets containing 10% of bene. Another group received 10 mg/kg busulfan and was fed with pellet containing 10% bene. Then, sperms, sperm chromatin quality, testicular histopathology, and oxidative stress levels were studied on the 35th day of the experiment. Results: Busulfan injection resulted in a significant reduction in sperm parameters compared to the control group (p<0.001); it decreased after bene administration (p<0.001). In addition, in the group treated with bene, the sperm count with damaged DNA was reduced and the level of malondialdehyde decreased compared to the busulfan group. A significant increase was observed in the mean level of superoxide dismutase and catalase enzymes in the bene + busulfan group compared to the busulfan group (p<0.001). The histopathological improvement of the testis was observed in the bene + busulfan group. Conclusion: The administration of 10 mg/kg of bene powder for 35 days reduced the oxidative stress, improved testicular histopathology, sperm chromatin quality, and sperm parameters in the infertile mice model.